Peranan dan Eksistensi Yurisprudensi dalam Sistem Hukum di Indonesia - Junaedi (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2023)
Understanding the importance of jurisprudence in relation to the role of judges in processing a case in court, this all indicates that jurisprudence is an inseparable part when a judge processes a case to make a decision when the written legal rules are not textually stated. And this is also the principle of freedom of action for judges, when the legal text does not stipulate concretely, this is all done to fill the legal vacuum. However, what needs to be considered is the principle of freedom of action (freies ermeseen / discretion) for a state official (judge), may not act as freely as he or she wills, but the freedom to act must result in legal decisions that are guided by the value of control, the value of benefit and the value of certainty to be able to do so. felt by all components of society. Thus, the role and existence of jurisprudence in the legal system in Indonesia is highly expected to build and enforce social justice laws for all Indonesian people. For this reason, a legal problem arises, what is the role and existence of jurisprudence in the Indonesian legal system? This requires a firm, clear, and concrete legal reasoning so that in practice the law can be touched by all levels of Indonesian society.